2011
DOI: 10.1167/iovs.11-7509
|View full text |Cite
|
Sign up to set email alerts
|

Rod Sensitivity, Cone Sensitivity, and Photoreceptor Layer Thickness in Retinal Degenerative Diseases

Abstract: Both rods and cones can support an intact IS/OS junction and normal photoreceptor thickness measures. The product of ONL and OS thicknesses is proportional to the sensitivity mediated by the less abnormal type of photoreceptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 19 publications
5
73
1
Order By: Relevance
“…Overall, the SD-OCT changes observed in CDSR are nonspecific, and similar changes have been described in achromatopsia, cone dystrophy, cone-rod dystrophy, and ABCA4-related disease. [42][43][44][45] The rod b-wave to low flash strength (DA 0.002) was nonrecordable or markedly delayed; rod b-wave to DA2.29 ERG was high or supernormal as previously reported. 5 Disproportionately large increments in rod b-wave amplitude with small increments in flash strengths (across the range tested) were evident only in a subset; an insufficient number of intermediate strength flashes likely precluded observance of the same in the rest.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, the SD-OCT changes observed in CDSR are nonspecific, and similar changes have been described in achromatopsia, cone dystrophy, cone-rod dystrophy, and ABCA4-related disease. [42][43][44][45] The rod b-wave to low flash strength (DA 0.002) was nonrecordable or markedly delayed; rod b-wave to DA2.29 ERG was high or supernormal as previously reported. 5 Disproportionately large increments in rod b-wave amplitude with small increments in flash strengths (across the range tested) were evident only in a subset; an insufficient number of intermediate strength flashes likely precluded observance of the same in the rest.…”
Section: Discussionsupporting
confidence: 74%
“…S À was measured in NPHP5-LCA patients. The structure-function data from the different genotypes were plotted, and we applied a simple linear model which has been used to describe this relationship in various retinal degenerations (21)(22)(23)(24). The results indicated that central disease due to BBS1, USH2A and RPGR mutations behaved similarly and like pure photoreceptor degenerations.…”
Section: Resultsmentioning
confidence: 99%
“…11 This may be due to the increase in ellipsoid volume with increasing eccentricity 51 and the absence of rods at the fovea, which also contributes to the intensity of the EZ band. 11,58 To accommodate for the automatic brightness adjustments to SD-OCT images, the ELM and INL were chosen as references. These structures are considered to remain relatively unaltered in early disease.…”
Section: Discussionmentioning
confidence: 99%